2018
DOI: 10.1038/s41419-018-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

Alarmin HMGB1 induces systemic and brain inflammatory exacerbation in post-stroke infection rat model

Abstract: Post-stroke infection (PSI) is known to worsen functional outcomes of stroke patients and accounts to one-third of stroke-related deaths in hospital. In our previous reports, we demonstrated that massive release of high-mobility group box protein 1 (HMGB1), an endogenous danger signal molecule, is promoted by N-methyl-d-aspartic acid-induced acute damage in the postischemic brain, exacerbating neuronal damage by triggering delayed inflammatory processes. Moreover, augmentation of proinflammatory function of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 50 publications
3
31
1
Order By: Relevance
“…In our study, we showed that it is possible to perform Western blot assays to analyse the expression of HMGB1 redox isoforms both at cell and tissue levels. Other studies reported the detection of HMGB1 redox isoforms in serum and plasma by Western blot assay (31,32), showing that this method can also be applied to extracellular fluids. Western blot has a wide range of applications in the clinic, such as the application of medical diagnosis for FIGURE 5 | Redox modulation of HMGB1 in spleen and in drug-intoxicated liver.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed that it is possible to perform Western blot assays to analyse the expression of HMGB1 redox isoforms both at cell and tissue levels. Other studies reported the detection of HMGB1 redox isoforms in serum and plasma by Western blot assay (31,32), showing that this method can also be applied to extracellular fluids. Western blot has a wide range of applications in the clinic, such as the application of medical diagnosis for FIGURE 5 | Redox modulation of HMGB1 in spleen and in drug-intoxicated liver.…”
Section: Discussionmentioning
confidence: 99%
“…Once there are infections or tissue injuries, HMGB1 can be upregulated by immune cells or necrotic cells (Lotze and Tracey, 2005). In cerebral ischemia/reperfusion processes, it triggers delayed inflammation and exacerbates neuron damage (Kim et al, 2018). On the other hand, the NF-kB family, consisting of transcription factors, and its associated signaling pathway play a complex but crucial role in the regulation of immune response (Tilborghs et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One study confirmed overstimulation of cardiac sympathetic innervation using the catecholamine synthesis rate-limiting enzyme tyrosine hydrolase. 7 Sympathetic hyperstimulation also blunts vagal influence, as confirmed in stroke patients via heart rate variability testing. 61 HPA activation and hypothalamic paraventricular nucleus output also prompted cardiac arrhythmias and impaired cardiac output in rat models.…”
Section: Cardiovascular Dysfunctionmentioning
confidence: 95%
“…6 AIS research has historically focused on these central nervous system (CNS) interventions to reduce infarct volume and address neuronal viability. More re-cently, however, detrimental effects of AIS on the heart 7 and immune system 8 have gained popularity. Indeed, medical complications following AIS such as pneumonia are strong predictors of mortality and functional outcome.…”
Section: Introductionmentioning
confidence: 99%